EXPERIMENTAL INVESTIGATION AND MODELLING OF SURGE/SWAB PRESSURE FOR NON-NEWTONIAN FLUIDS - KRISHNA, SHWETANK (2021)
The motivation of this research arises from the constrained understanding of non- Newtonian fluid rheological parameters and drilling design variables on the prediction of surge/swab pressure during pipe tripping operation.